PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA TOKO SX SEPATAN (Studi Pada Konsumen Toko Offline Di Kabupaten Tangerang) - Eko Sugiyanto; Aditirangga; Unsi Fitriyah; Jessica Timmiane Abigail (JURNAL LENTERA BISNIS, 2024)
This research aims to determine the influence of service quality, price and customer satisfaction partially or simultaneously. The sample for this research was 100 respondents where they were visitors to the XS Sepatan store. The technique used is total sampling. The data collection technique uses a questionnaire whose validation and reliability have been tested. The analysis technique used is multiple linear regression analysis. The results of this research show that: (1) Service Quality has a positive and significant influence on Customer Satisfaction as evidenced by the Service Quality variable (X1) having a calculated t value of 3.742 > t table 1.984 with a significance level of 0.000 < 0.05. (2) Price is positive but has no influence on Customer Satisfaction as evidenced by the Price variable (X2) having a calculated t value of 1.169 < 1.984 with a significance level of 0.245 > 0.05. (3) Customer Satisfaction has a positive and significant influence. This can be proven from the calculated f value of 11, 187 > f table 3.09 with a significant value of 0.000 < 0.05. The results of the analysis are expected to provide useful information for business people in improving service quality, product pricing and customer satisfaction regarding proper business management.